ANTIOXIDANT ACTIVITY OF HYDROALCOHOLIC EXTRACT OF GREEN GEDI LEAVES (Abelmoschus manihot L.) USING CUPRAC (CUPRIC ION REDUCING ANTIOXIDANT CAPACITY) METHOD - Kaban, Vera Estefania; Nasri, Nasri; Suci, Nurul; Lubis, Muhammad Fauzan; Rani, Zulmai; Nasution, Haris Munandar (Indonesian Journal of Pharmaceutical and Clinical Research, 2025)
Free radicals induce oxidative stress, which plays a pivotal role in the pathogenesis of various degenerative diseases. Abelmoschus manihot L., locally known as green gedi, is recognized for its rich secondary metabolite content with potential antioxidant properties. This study aimed to evaluate the antioxidant activity of the hydroalcoholic extract of green gedi leaves using the Cupric Ion Reducing Antioxidant Capacity (CUPRAC) method. Extraction was conducted via maceration using a 90% hydroalcoholic solvent, followed by comprehensive phytochemical screening and simplicia characterization. The antioxidant capacity was quantified by determining the IC50 value through linear regression analysis of inhibition percentage versus concentration. Phytochemical analysis confirmed the presence of alkaloids, flavonoids, glycosides, saponins, tannins, and triterpenoids/steroids. The hydroalcoholic extract exhibited "very strong" antioxidant activity, yielding an IC50 value of 41.65 ± 0.30 µg/mL. Although this potency was slightly lower than the pure quercetin standard, it demonstrates a significant capacity for free radical neutralization. These findings underscore the potential of Abelmoschus manihot L. as a robust natural antioxidant source, supporting its further development into phytopharmaceuticals or functional health supplements for the prevention of oxidative stress-related conditions.